Programa de transformación productiva (PTP): pilar fundamental para la línea de emprendimiento y empresarismo del grupo CINDE de la Fundación Universidad de América (2014)
The academy cannot be indifferent to this transformation of the productive apparatus of the country and that is why the research groups of educational institutions, should be aware of this program, focusing its efforts and research projects on strategic sectors identified by the PTP. Therefore, the line of enterprise and entrepreneurship, of the research group CINDE of the University of America Foundation, will be not the exception, and now a days, it articulate its mission and projects made such strategic sectors.